Establishing reference values for percentage of appendicular skeletal muscle mass and their association with metabolic syndrome in Korean adolescents - Da Hye Lee; Sung-Chan Kang; Seung-Sik Hwang; Yun Jeong Lee; Hwa Young Kim; Seong Yong Lee; Choong Ho Shin; Jaehyun Kim (Korean Society of Pediatric Endocrinology, 2023)
Purpose The association between appendicular skeletal muscle mass (ASM) and cardiometabolic risk has been emphasized. We estimated reference values of the percentage of ASM (PASM) and investigated their association with metabolic syndrome (MS) in Korean adolescents. Methods Data from the Korea National Health and Nutrition Examination Survey performed between 2009 and 2011 were used. Tables and graphs of reference PASM were generated using 1,522 subjects, 807 of whom were boys aged 10 to 18. The relationship between PASM and each component of MS in adolescents was further analyzed in 1,174 subjects, 613 of whom were boys. Moreover, the pediatric simple MS score (PsiMS), the homeostasis model assessment of insulin resistance (HOMA-IR), and the triglyceride-glucose (TyG) index were analyzed. Multivariate linear and logistic regressions adjusting for age, sex, household income, and daily energy intake were performed. Results In boys, PASM increased with age; the trend was different in girls, in whom PASM declined with age. PsiMS, HOMA-IR, and TyG index showed inverse associations with PASM (PsiMS, β=-0.105, P<0.001; HOMA-IR, β=-0.104, P<0.001; and TyG index, β=-0.013, P<0.001). PASM z-score was negatively associated with obesity (adjusted odds ratio [aOR], 0.22; 95% CI, 0.17-0.30), abdominal obesity (aOR, 0.27; 95% CI, 0.20-0.36), hypertension (aOR, 0.65; 95% CI, 0.52-0.80), and elevated triglycerides (aOR, 0.67; 95% CI, 0.56-0.79). Conclusions The probability of acquiring MS and insulin resistance decreased as PASM values increased. The reference range may offer clinicians information to aid in the effective management of patients. We urge clinicians to monitor body composition using standard reference databases.